Early estimated glomerular filtration rate and depression in kidney transplantation recipients: a longitudinal study. Issue 9 (21st October 2021) - Wu, Xiaoqi; Liu, Min; Cui, Lina; Liu, Jia; Liu, Lifang; Wu, Xiaoxia; Wang, Zhimin; Cheng, Andy Sk; Xie, Jianfei; Li, Xiaolian
ABSTRACT: Depression is a common psychological problem in kidney transplantation (KT) recipients and affects long-term graft outcomes. Estimated glomerular filtration rate (eGFR) as a commonly used indicator of renal function plays a vital role in follow-up detection after KT. The aim of this study is to observe the change of early eGFR within 3 months after KT and to explore the correlation between eGFR and depression before and after transplantation. The Self-rating Depression Scale was used to evaluate depression. Among 135 patients with KT, 128 patients completed the longitudinal study. We used a one-way repeated-measures analysis of variance to analyze eGFR and a generalized estimating equation model to examine the relationship between depression and eGFR in KT recipients with pre-transplant and 30, 60, 90 days post-transplant. The mean eGFR of KT recipients at four time-points was 5.97 ± 4.83, 72.84 ± 26.06, 79.06 ± 26.45 and 81.79 ± 25.62, respectively. The results demonstrated that eGFR kept steady at 60 days and 90 days post-transplant; depression was significantly associated with eGFR. Earlier identification and treatment of depression in KT recipients may be essential to promote their recovery of early renal function.